Gendang Habsyi sebagai Sarana Menumbuhkan Minat Seni Islami pada Anak SD - Rabiatun Ummi Rabiah; Isnaeni Maulidiati Rahmah; Istiyati Mahmudah (Lembaga Pengembangan Kinerja Dosen, 2025)
Instilling Islamic art values ​​from an early age is a strategic step in shaping children's character based on local spiritual and cultural values. One potential approach to achieving this goal is through the introduction and learning of traditional Islamic musical instruments, such as the gendang habsyi. The gendang habsyi, as a musical instrument that is identical to the poems of praise to the Prophet Muhammad SAW, has high educational and spiritual value, and is able to attract children's interest through its rhythmic and interactive elements. This article aims to examine the role of the gendang habsyi in fostering elementary school children's interest in Islamic art, both from musical, educational, and social aspects. Using a descriptive qualitative approach, this study involved observation and interviews with art teachers, students, and parents at an Islamic elementary school. The findings show that the introduction of the gendang habsyi is not only able to arouse children's interest in Islamic musical art, but also strengthen their love for Islamic culture, foster a spirit of togetherness, and increase children's self-confidence in expressing themselves positively. In addition, the fun and contextual learning method through the habsyi drum game has proven effective in building an inclusive and meaningful learning atmosphere. Therefore, the integration of habsyi drums in the art curriculum at the elementary school level is worth considering as one of the strategic alternatives in Islamic art education based on local culture.